Comparing mental toughness: An investigation on elite Indian standing and seated para-thrower athletes - Vikas Singh; Tenzing Norzom Bhutia; Mahendra Kumar Singh; Pawan Bisht; Harish Singh; Cicelia Mohan Thomas (AOSIS, 2022)
Having psychological advantage that enables athletes to perform at their best regardless of challenges and adversity is what is meant by having mental toughness (MT). In order to better understand the mental toughness of elite Indian standing and sitting para-thrower athletes, this study looked at a variety of mental sub - scales. Elite para-throwers who competed at the international level, consider making up the sample of the current study; which includes a total of nine elite para-throwers [5 Standing Para-throwers (StPT) and 4 Seated Para-throwers (SePT)]. The researcher used the Psychological Performance Inventory (PPI), designed by Loehr, and the Personal Demographic Information form to gather data in order to ascertain the participants' attitudes of mental toughness. An independent T-test with 0.05 significance level was performed for the research's findings, there are no statistical significant difference between the two groups' levels of motivation, self-confidence, ability to control negative energy, attention, visualisation, ability to control positive energy, and attitude control factors of MT. Elite Indian para-thrower athletes' mental toughness is similar in both groups, with no discernible differences.